AN INVESTIGATION OF FACTORS INFLUENCING THE GROWTH OF FINANCIAL LITERACY AMONG SMALL SCALE TRADERS IN THE CENTRAL BUSINESS DISTRICT OF LUSAKA - Vincent Kayangula; Dewin Arona Sikalumbi (International Journal of Innovative Technologies in Social Science, 2025)
The study aimed to investigate the factors influencing the growth of financial literacy among the small-scale traders in the Central Business District in Lusaka. The study’s main objective was to determine the factors that influence the growth of financial literacy offered by financial institutions to the small-scale traders; and to assess effects of financial literacy among small scale traders (CBD) in Lusaka; to establish measures that can be used to address factors that influence growth of financial literacy among small scale traders in the Central Business District in Lusaka. The study adopted a mixed methodology approach because it resides in the middle of both qualitative and quantitative continuum and because it also incorporates elements of both qualitative and quantitative approaches. Purposive sampling technique was used to select 137 respondents from the Central Business District (CBD) of Lusaka to be included in the study. Data collection involved both secondary and primary data; the primary data was collected from respondents such as business owners, managers and workers. Questionnaires, face-to-face interviews and literature review methods were used for data collection. The findings of the study show that factors of financial literacy include financial knowledge, financial attitude and financial awareness. The study shows that financial literacy positively contributes to the growth of business organizations for the small-scale traders in the Central Business District of Lusaka. The study recommends that training of small small-scale traders should be effected since majority of the traders are in the informal sector and their businesses survive for many years but with minimal growth, due to lack of financial knowledge. Finally, the study recommends that government work towards streamlining the coordination of institutions implementing SMEs activities and further research can be carried out to find out the challenges faced by financial literacy providers while undertaking financial education to small-scale traders.